ISTINBATH HUKUM PERNIKAHAN BEDA AGAMA MENURUT RASYID RIDHA DAN YUSUF AL-QARDHAWI - Al Banan, Abal Qosim; Mustofa, Imron; Solikin, Agus (Institut Agama Islam Negeri (IAIN) Pontianak, 2024)
This study aims to: 1) Investigate the methods of Islamic legal reasoning employed by Muhammad Rashid Rida and Yusuf Al-Qardhawi in the context of interfaith marriage, and 2) Assess the relevance and applicability of the legal reasoning approaches of these two scholars in addressing contemporary legal issues. This study employs a qualitative approach using a literature review method, where the researcher analyzes the writings and fatwas of both scholars as well as relevant secondary sources. The data analysis technique used is content analysis, focusing on methods of Islamic legal reasoning such as ta'lil, qiyas, istishab, and istihsan. The research findings indicate that: 1) Muhammad Rashid Rida tends to use the methods of qiyas and istihsan, considering broader benefits and maslahah, while Yusuf Al-Qardhawi relies more on ta'lil and istishab, emphasizing the importance of maintaining the integrity and order of existing Islamic law. 2) The different approaches to legal reasoning between the two scholars reflect their views on social dynamics and the needs of the community, demonstrating their relevance and applicability in responding to contemporary issues and the importance of constructive dialogue among various Islamic perspectives.